Research and Development of Organic Phase Change Materials for Cool Thermal Energy Storage - Tao Wenbo; Xie Ruhe (Zhileng xuebao, 2016)
Research and development of organic phase change materials (PCMS) and inorganic-organic PCMS are reviewed. The method of using the formula to guide the ratio of low eutectic phase change thermal storage material is discussed, and a method is presented to improve thermal conductivity of organic phase change materials. The application of phase change materials in the fields of solar energy utilization, electricity peak shift, air conditioning energy conservation and refrigerated transport is stated. It is pointed out that performance characteristics, theoretical model of heat transfer, phase transition mechanism and composite technology of PCMs should be focused on, and organic composite phase change thermal storage material is the key development direction of organic phase change materials in the future.